Reinventing project-based learning - Boss, Suzie (International Society for Technology in Education, 2007)
Includes bibliographical references (p. 191-194) and index.; Mapping the journey--seeing the big picture -- Creating a professional learning community -- Imagining the possibilities -- Strategies for discovery -- Project management strategies for teachers and learners -- Project launch--implementation strategies -- A guiding hand--keeping a project moving -- Building connections and branching out -- Making assessment meaningful -- Celebrating and reflecting -- Bringing it home.; Offers educators a guide for maximizing the benefits of project-based learning in today's technology-rich learning environment.